2001
DOI: 10.1152/ajpregu.2001.281.4.r1302
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the afferent limb of the vesicovascular reflex using neurotoxins, resiniferatoxin and capsaicin

Abstract: The afferent limb of the vesicovascular reflex (VV-R) evoked by distension or contraction of the urinary bladder (UB) was studied in urethane-anesthetized female rats by examining the changes in VV-R after administration of C-fiber afferent neurotoxins [capsaicin and resiniferatoxin (RTX)]. Systemic arterial blood pressure increased parallel (5.1 to 53.7 mmHg) with graded increases in UB pressure (20 to 80 cm H(2)O) or during UB contractions. The arterial pressor response to UB distension was significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…Normal voiding has been shown to be dependent on Aδ-fiber bladder afferents, whereas Cfiber afferents are responsible for bladder nociceptive responses 16,17 . The previous and successful use of Neurometer® and measurement of current perception threshold (CPT) in cutaneous afferent sites [13][14][15] makes this technique an attractive modality to assess the status of the specific afferent nerve fibers in the bladder or other visceral organs.…”
Section: Discussionmentioning
confidence: 99%
“…Normal voiding has been shown to be dependent on Aδ-fiber bladder afferents, whereas Cfiber afferents are responsible for bladder nociceptive responses 16,17 . The previous and successful use of Neurometer® and measurement of current perception threshold (CPT) in cutaneous afferent sites [13][14][15] makes this technique an attractive modality to assess the status of the specific afferent nerve fibers in the bladder or other visceral organs.…”
Section: Discussionmentioning
confidence: 99%
“…The best ICP value was divided by simultaneous mean arterial pressure (ICP/AP) that was measured during the period of electrostimulation of pelvic nerve, because pelvic nerve stimulation possibly increased AP due to activation of pelvic nerve afferents to induce pressor responses such as that known as the vesico-vascular reflex. 62 ICP/AP was measured at 2 or 4 weeks after the nerve injury. After the ICP measurement, the bilateral MPG was dissected out and histological studies were performed.…”
Section: Icp and Ap Measurementmentioning
confidence: 99%
“…3 These earlier results indicated that the bladder-to-vascular reflex is induced by the activation of C-fiber bladder afferent pathways during bladder distention of normal rats. The current study extends the earlier findings to rats with SCI induced by complete Th4-5 spinal cord transection.…”
Section: Discussionmentioning
confidence: 85%
“…3 In brief, PE-50 tubing (Clay-Adams, Parsippany, NJ, USA) was inserted into the bladder through the urethra and tied in place by a ligature around the urethral orifice. Then the PE-50 tubing in the urethra was connected via a three-way stopcock to a pressure transducer and to a syringe pump for recording intravesical pressure and for infusing saline into the bladder, respectively.…”
Section: Bladder-to-vascular Reflex During Bladder Distentionmentioning
confidence: 99%
See 1 more Smart Citation